Development of Management Information System in Education in the Globalization Era - Hasanuddin, Hasanuddin; Iskandar, Dadang Ishak; Rumianti, Susti (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
This research aims to compare the development of educational information systems. As time goes by, educational information systems are the most important aspect in the world of education and are most needed because educational management information systems support the progress of formal and informal educational institutions. Meanwhile, this article is the result of a qualitative study, examining various sources related to the implementation of management information systems and of course various phenomena in the development of educational management information systems and their use in the world of education today and also in the environment. Keywords: Development, Management information systems, Education, Globalization